Pembelajaran Hadis untuk Anak Usia Dini - Nuryati, Nuryati (ACIECE, 2017)
The article describes the study of Hadith for early childhood, which is inclusive in a lesson.Research subject is a child of group B. This research is a qualitative research with research typeof phenomenology study. Data analysis used is Mills and Huberman model. Research data wereobtained from observation, interview, documentation, and field notes. The results of this studyindicate that: (1) In the process of developing spiritual intelligence using the material as teachingmaterials, using methods in learning and using evaluation as an assessment in the developmentof spiritual intelligence, (2) Hadis teaching materials for early childhood such as hadith intention,hadith Say greetings, hadith affection, hadis keeping verbal, hadith hygiene and hadith beauty.While the method used is the method drill, exemplary, habituation, lecture, story telling, play,and assignment. Then the evaluation used is observation, anecdotal notes, test of deed and oraltest